2020
DOI: 10.1038/s41467-020-19575-2
|View full text |Cite
|
Sign up to set email alerts
|

ST3GAL1 is a target of the SOX2-GLI1 transcriptional complex and promotes melanoma metastasis through AXL

Abstract: Understanding the molecular events controlling melanoma progression is of paramount importance for the development of alternative treatment options for this devastating disease. Here we report a mechanism regulated by the oncogenic SOX2-GLI1 transcriptional complex driving melanoma invasion through the induction of the sialyltransferase ST3GAL1. Using in vitro and in vivo studies, we demonstrate that ST3GAL1 drives melanoma metastasis. Silencing of this enzyme suppresses melanoma invasion and significantly red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 62 publications
4
61
0
Order By: Relevance
“…Chromatin immunoprecipitation assay showed cooccupancy of both TFs at a distal enhancer element located at about 10 kb upstream ST3GAL1 transcription start site. Consistently, authors demonstrated that ST3GAL1 mediates SOX2-and GLI1-induced melanoma invasiveness [21]. This study suggests that regulatory regions other than promoters are involved in transcriptional regulation of ST3GAL1.…”
Section: Regulation Of Sialyltransferase Gene Expressionsupporting
confidence: 65%
See 1 more Smart Citation
“…Chromatin immunoprecipitation assay showed cooccupancy of both TFs at a distal enhancer element located at about 10 kb upstream ST3GAL1 transcription start site. Consistently, authors demonstrated that ST3GAL1 mediates SOX2-and GLI1-induced melanoma invasiveness [21]. This study suggests that regulatory regions other than promoters are involved in transcriptional regulation of ST3GAL1.…”
Section: Regulation Of Sialyltransferase Gene Expressionsupporting
confidence: 65%
“…Silencing of ST3GAL1 suppressed melanoma migration and invasion, and reduced the ability of aggressive melanoma cells to enter the bloodstream, colonize distal organs and survive in the metastatic environment, without affecting melanoma cell proliferation nor orthotopic tumor growth in vivo. Mass spectrometry and functional assays revealed that ST3GAL1 explicates the pro-invasive functions through the receptor tyrosine kinase AXL, and that ST3GAL1-mediated sialylation is able to induce AXL dimerization and activation [21].…”
Section: Sustainingmentioning
confidence: 99%
“…Accordingly, activation of the GLI-SOX2 axis is involved in gemcitabine resistance in pancreatic cancer [ 33 ]. Recently, a reciprocal regulation between SOX2 and GLI1 has been described to fuel aberrant glycosylation/sialylation during melanoma progression [ 34 ]. Altogether, these reports and the present study highlight the importance and the biological relevance of the mutual regulation between SOX2 and GLI transcription factors in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, in this study we provide evidence of a novel mechanism of non-canonical SMO-independent activation of GLI1 by the SOX2-BRD4 axis and describe the efficacy of a combinatorial treatment with a novel SMO inhibitor and the PROTAC-derived BRD4 degrader MZ1 in melanoma. The existence of a reciprocal regulation between SOX2 and GLI1 [ 31 ] (this study), which is involved in the transcriptional activation of genes involved in melanoma progression [ 34 ], highlights the therapeutic potential of targeting this axis to treat a subset of advanced melanomas expressing high levels of SOX2 and GLI1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation